The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12223-017-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the interactions and phytotoxicity of zinc oxide nanoparticles with agriculturally beneficial bacteria and selected crop plants

Abstract: There is a growing interest in the use of bioinoculants to assist mineral fertilizers in improving crop production and yield. Azotobacter and Pseudomonas are two agriculturally relevant strains of bacteria which have been established as efficient bioinoculants. An experiment involving addition of graded concentrations of zinc oxide (ZnO) nanoparticles was undertaken using log phase cultures of Azotobacter and Pseudomonas. Growth kinetics revealed a clear trend of gradual decrease with Pseudomonas; however, Azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Microbial populations are greater in the rhizosphere, the region around the root influenced by exudation of plant metabolites, than in the surrounding soil . These plant exudates provide nutrients to support microbial growth. However, the complex microbial community structure in soils is disturbed by NP amendments, with both increases and decreases for certain taxa occurring dependent on NP, plant, and soil properties. , The soil microbes involved in the nitrogen cycle are among those with documented sensitivity. Changes in function of a population, such as a loss in function of nitrogen-fixing rhizobium isolates, would in turn affect plant performance. ,, Clearly, any formulation for agricultural use should not have deleterious effects on the organisms involved in essential element cycling …”
Section: Introductionmentioning
confidence: 99%
“…Microbial populations are greater in the rhizosphere, the region around the root influenced by exudation of plant metabolites, than in the surrounding soil . These plant exudates provide nutrients to support microbial growth. However, the complex microbial community structure in soils is disturbed by NP amendments, with both increases and decreases for certain taxa occurring dependent on NP, plant, and soil properties. , The soil microbes involved in the nitrogen cycle are among those with documented sensitivity. Changes in function of a population, such as a loss in function of nitrogen-fixing rhizobium isolates, would in turn affect plant performance. ,, Clearly, any formulation for agricultural use should not have deleterious effects on the organisms involved in essential element cycling …”
Section: Introductionmentioning
confidence: 99%
“…ZnO‐NPs are amongst NPs with high production volume and therefore a high environmental release risk . In soil, it may have a selective deteriorating effect on certain beneficial microorganisms . In this study, it has been found that ZnO‐NPs treatment in low concentration (1 μg ml −1 ) neither had a severe effect on the OTUs in soil samples, specially, Bacillus sp.…”
Section: Discussionmentioning
confidence: 60%
“…With the dramatic increase in the use of NPs, a new approach for the environmental risk assessment of NPs is urgently needed . Treatment of soil with NPs usually results in antimicrobial effect on certain valuable soil microorganisms in particular or overall microbial community . We are much concerned with the impact of NPs and their serious effects on microbial community structure and natural biodegradation process provided by endogenous bacterial populations in contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion of hydrophobic nanoparticles into lipid membranes poses a great challenge since the membranes are destroyed during the loading process [46,47]. Macroscopically visible effects include curving of the lipid membrane, budding or fission effects [48,49]. Negatively charged nanoparticles often result in clustering effects thus reducing charge movement/transfer and increasing the gel phase of the involved lipids [50].…”
Section: Interaction Of Polymers and Nanoparticles With Membranesmentioning
confidence: 99%